A flash of Hex - Battis, Jes, 1979- (New York : Ace Books, 2009)
"As an Occult Special Investigator, Tess Corday has seen her fair share of disturbing crime scenes--but nothing has ever shocked her as much as the ritualistic murder of a drugged-out runaway kid, who she soon learns was not the first such victim. All the dead teens had traces of the dangerous magical drug called Hex in their bodies. All were the children of powerful mage families. All were killed with the sacred tools of mages. It adds up to the chilling possibility that the OSI is dealing with a serial killer, one who has incredible inhuman powers. To stop the slaughter, Tess and her partner, Derrick, will go anywhere and do anything--including seeking help from the necromancer Lucian Agrado, whom Tess is under orders to avoid. But as the deaths continue, Tess becomes convinced that the identity of the killer is locked inside her own head. And the question is, how many rules is she willing to break to get to the truth?"
Sequel to: Night child.
Keywords: Magic -- Fiction; Serial murders -- Fiction; Murder -- Investigation -- Fiction; Fantasy fiction; Occult fiction